Mrs. Berenson, Mrs. Gardner and Miss Toplady: Connoisseurship, Collecting and Commerce in London (1898–1905). (3rd April 2017) - Israëls, Machtelt Brüggen
Abstract : This article uses primary material including letters and diary entries to reconstruct the activity of a London curiosity shop called Miss Toplady that operated between 1898 and 1905. Foremost among its founders were the art critic Mary Berenson née Smith and her brother, the author Logan Pearsall Smith. As one of the early fronts that Mary and Bernard Berenson used for selling art, the shop affected the development of their expertise as connoisseurs, and vice versa. As a place that was not only instrumental in transactions with the collector Isabella Stewart Gardner in Boston but was also frequented by writers and academics, the establishment helped give Italian art and antiques an international and literary cachet.